Impact of COVID-19 on the prevalence of dyslipidemia in Ecuador: A cross-sectional study between 2017 and 2022 - Josue Rivadeneira; Luis Fuenmayor-González; Michelle Jácome-García; Nancy Flores-Lastra; Hugo Delgado; Tamara Otzen (Atención Primaria)
Objective: To determine changes in the prevalence of dyslipidemias during the pre-COVID-19 and COVID-19 years in three regions of Ecuador. Design: Cross-sectional study. Site: Quito, Guayaquil, and El Coca. Participants: Adults with cholesterol, HDL, LDL, and triglyceride levels at primary care centers from January 2017 to December 2022. Interventions: Not applicable. Main measurements: Data were obtained from five BIODIMED primary care centers. Cholesterol, HDL, LDL, and triglyceride levels were classified according to the ATP III guidelines. Dyslipidemia was considered present when one or more parameters exceeded specific thresholds. Sociodemographic variables and the year of examination were included as independent variables. Results: The study analyzed 110,521 participants’ laboratory results, where 65.3% were males and an average age of 38 ± 12 years. The study spanned the Andean (72.4%), Coast (15.4%), and Amazonic region (12.3%). Pre-pandemic exams constituted 60.9% of the sample. The prevalence of dyslipidemia increased gradually from 43.1% in 2017 to 64.1% in 2022. Cholesterol levels, HDL, and LDL exhibited changes during the pandemic, with an increased risk of hypercholesterolemia, low HDL, and high LDL. Conclusions: During the COVID-19 pandemic, a notable increase in the prevalence of dyslipidemias, including hypercholesterolemia, high triglycerides, and high LDL, was determined across three regions in Ecuador. Resumen: Objetivo: Determinar los cambios en la prevalencia de dislipidemias durante los años previos a la COVID-19 y durante la misma en tres regiones de Ecuador. Diseño: Estudio transversal. Ubicación: Quito, Guayaquil y El Coca. Participantes: Adultos con niveles de colesterol de lipoproteínas de alta densidad (HDL), de lipoproteínas de baja densidad (LDL) y triglicéridos en centros de atención primaria desde enero de 2017 hasta diciembre de 2022. Intervenciones: No aplica. Principales mediciones: Los datos se obtuvieron de cinco centros de atención primaria BIODIMED. Los niveles de colesterol HDL, LDL y triglicéridos se clasificaron según las directrices del Adult Treatment Panel III (ATP III). Se consideró que existía dislipidemia cuando uno o más parámetros superaban los umbrales específicos. Se incluyeron variables sociodemográficas y el año de examen como variables independientes. Resultados: El estudio analizó los resultados de laboratorio de 110.521 participantes, donde el 65,3% eran hombres y la edad promedio era de 38 ± 12 años. El estudio abarcó la región Andina (72,4%), la Costa (15,4%) y la región Amazónica (12,3%). Los exámenes prepandemia constituyeron el 60,9% de la muestra. La prevalencia de dislipidemia aumentó gradualmente del 43,1% en 2017 al 64,1% en 2022. Los niveles de colesterol HDL y LDL mostraron cambios durante la pandemia, con un riesgo aumentado de hipercolesterolemia, HDL bajo y LDL alto. Conclusiones: Durante la pandemia de COVID-19, se determinó un aumento notable en la prevalencia de dislipidemias, incluyendo hipercolesterolemia, triglicéridos altos y LDL alto, en tres regiones de Ecuador.